Corrosion of Cr23C6 coated Q235 steel in wet atmospheres containing Na2SO4 at 750 °C. (November 2015) - Wu, Shoujun; Fei, Yunlong; Guo, Bin; Jing, Lina
Highlights: Corrosion of Cr23 C6 coated Q235 was studied in wet atmosphere and also containing Na2 SO4 at 750 °C. Corrosion generated small quantities of Cr2 O3 and Cr7 C3 and changed the surface morphology of the coating from granular to scale-like. Corrosion took place on the surface and the Cr23 C6 coating has favorable corrosion resistance. Abstract: The corrosion of a Cr23 C6 -coated Q235 steel was studied in environments containing Na2 SO4, O2, and water vapor at 750 °C. The Cr23 C6 -coated sample showed parabolic weight gains during both corrosion and wet oxidation. However, the weight gain during wet oxidation was much greater than that during corrosion. Corrosion generated small quantities of Cr2 O3 and Cr7 C3 and changed the surface morphology of the coating from granular to scale-like. Corrosion took place on the surface, and the consumption of the Cr23 C6 coating occurred very slowly. The results indicate that the Cr23 C6 coating has favorable corrosion resistance.